2010
DOI: 10.1186/1471-2164-11-86
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic and proteomic analyses of two Mycoplasma agalactiae strains: clues to the macro- and micro-events that are shaping mycoplasma diversity

Abstract: BackgroundWhile the genomic era is accumulating a tremendous amount of data, the question of how genomics can describe a bacterial species remains to be fully addressed. The recent sequencing of the genome of the Mycoplasma agalactiae type strain has challenged our general view on mycoplasmas by suggesting that these simple bacteria are able to exchange significant amount of genetic material via horizontal gene transfer. Yet, events that are shaping mycoplasma genomes and that are underlining diversity within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(119 citation statements)
references
References 63 publications
3
115
1
Order By: Relevance
“…Furthermore, within individual species, the dendrograms generated from the MALDI-TOF MS spectra achieved epidemiologically relevant strain clustering. For instance, the M. agalactiae strains were separated into two branches that correspond to the two reference strains, namely, PG2 and 5632, which are described as representing each end of the genetic spectrum encountered in M. agalactiae (30). The strains from wild ungulates, namely, Capra ibex or chamois, interestingly were grouped together, as was previously reported with the use of partial sequencing of a housekeeping gene (31).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, within individual species, the dendrograms generated from the MALDI-TOF MS spectra achieved epidemiologically relevant strain clustering. For instance, the M. agalactiae strains were separated into two branches that correspond to the two reference strains, namely, PG2 and 5632, which are described as representing each end of the genetic spectrum encountered in M. agalactiae (30). The strains from wild ungulates, namely, Capra ibex or chamois, interestingly were grouped together, as was previously reported with the use of partial sequencing of a housekeeping gene (31).…”
Section: Discussionmentioning
confidence: 95%
“…For instance, three strains of M. hominis were included, as this species is known to be highly heterogeneous (29). Both M. agalactiae PG2 type strain and 5632 were acquired as well, as they are considered to be situated at each end of the genetic spectrum encountered in M. agalactiae (30). This proved successful because, for instance, several strains from wild ungulates (e.g., Capra ibex) that are known to be genetically different from domestic ruminant strains (31) were correctly identified as M. agalactiae.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study comparing M. agalactiae strains using whole-genomic and proteomic approaches, the differential expression of some drp genes was found in association with the membrane fraction. These data suggested that this family may participate in generating surface diversity, with some drp genes presenting features of lipoproteins and being expressed and others serving as sequence reservoirs (34). Interestingly, the drp genes are part of the gene pool which has undergone HGT with members of the phylogenetically distant mycoides cluster.…”
Section: Vol 78 2010 Essential Genes Of M Agalactiae In Cell Cultumentioning
confidence: 99%
“…Remarkably, whole-genome sequence analysis has revealed that extensive horizontal gene transfer (HGT) events, affecting up to 18% of the M. agalactiae genome, occurred between M. agalactiae and members of the mycoides cluster, illustrating the unexpected plasticity and adaptability of the mycoplasma genome (44,45). Recent advances in whole-genome sequencing have greatly facilitated the study of mycoplasmas (2,33,34,44,45). Unfortunately, these data alone have been of little help in identifying the mechanism underlying diseases caused by mycoplasmas.…”
mentioning
confidence: 99%
“…The microorganism is believed to be unable to penetrate cells, although it is known to adhere tightly to the colonized epithelium (34,37). Despite recent in-depth genomic and proteomic analyses (7,27,40), which have led to fundamental insights into its genomic and proteomic composition, very few proteins of M. agalactiae have been proved to be virulence determinants. These include a family of variable surface proteins, named Vpma proteins (16), the immunodominant adhesin P40 (14), and P48, a homologue of the macrophage-activating lipopeptide (MALP) of M. fermentans (36).…”
mentioning
confidence: 99%